The lost letters of Pergamum : a story from the New Testament world - Longenecker, Bruce W.; Witherington, Ben, III, 1951- (Grand Rapids, Mich. : Baker Academic, 2003)
Introduces readers to the style of New Testament writings, the social and political world of Jesus and his first followers, and early Christian gatherings. Using the literary technique of correspondence through ancient letters, which comprise much of the New Testament, Longenecker mixes fact and fiction to paint an interesting and informative picture of the New Testament world and early Christianity.
As one nobleman to another -- A personal request -- To honor the emperor -- They proclaim a different Lord -- The reputations of three men -- Jesus seems a curious figure -- Jesus' naive and irresponsible views -- Communities of support and fellowship -- The contexts determined the contents -- A complete reversal of lifestyle -- A conduit of blessing for many -- The gods had other plans -- May his will be done -- The possessions of our common creator.
Keywords: Luke, -- Saint -- Fiction; Church history -- Primitive and early church, ca. 30-600 -- Fiction; Bible -- History of Biblical events -- Fiction; Evangelists (Bible) -- Fiction; Christian saints -- Fiction; Physicians -- Fiction; Christian fiction